Inadequate Helmet Fit Increases Concussion Severity in American High School Football Players. (May 2016) - Greenhill, Dustin A.; Navo, Paul; Zhao, Huaqing; Torg, Joseph; Comstock, R. Dawn; Boden, Barry P.
Background: There is limited information on the relationship between football helmet fit and concussion severity. Hypothesis: Poor helmet fit may predispose football players to a more severe concussion. Study Design: Descriptive epidemiology study. Level of Evidence: Level 3. Methods: Data from concussion injury reports were obtained from the National High School Sports-Related Injury Surveillance System over a 9-year period. Symptoms, duration, and helmet parameters (fit, interior padding) were analyzed for all first-time concussions. Results: Data from 4580 concussions were analyzed. Patients who suffered concussions with a helmet that did not fit properly (3.22%), as determined by an athletic trainer, had higher rates of drowsiness (RR, 1.46; P = 0.005), hyperexcitability (RR, 2.38; P = 0.047), and sensitivity to noise (RR, 1.88; P < 0.001); had more symptoms (5.34 vs 4.54, P = 0.004); and had longer symptom duration ( P = 0.04). Athletes with helmets lined with an air bladder had greater rates of sensitivity to light (RR, 1.13; P = 0.02), sensitivity to noise (RR, 1.25; P = 0.009), and longer symptom duration ( P = 0.004) compared with foam or gel liners. Conclusion: An improperly fitted football helmet is a risk factor for a concussion with more symptoms and of longer duration. Concussions of longer duration are also more common in players with an air bladder–lined helmet. Current high school football rules should mandate supervision and maintenance of helmet fit throughout the season, prior to impact. Clinical Relevance: Team physicians, athletic trainers, coaches, and high school officials should ensure proper oversight of helmet fit in high school athletes to decrease concussion severity and duration.